Exosomes carried miR-181c-5p alleviates neuropathic pain in CCI rat models - ZHANG,YU (2022)
Abstract Mesenchymal stem cells (MSCs) derived exosomes (Exos) are one of the most promising candidate for the treatment of this condition. However, the underlying molecular mechanism remains uncertain. Here we investigated the therapeutic effect of exosomal miR-181c-5p (ExomiR-181c-5p) on a rat model of neuropathic pain induced by sciatic nerve chronic constriction injury (CCI). In this study NP model was established using the CCI method. NP levels were assessed using PWT and PWL. Microarray analysis and RT-PCR were used to determine the relative expression of miR-181c-5p. MSC-derived exosomes were extracted using the total exosome isolation reagent characterized by WB and NTA. MiR-181c-5p was loading into Exos using electroporation. The inflammation response in microglia cells and CCI rats were assessed by ELISA assay respectively. Our study demonstrates that miR-181c-5p expression was obviously decreased in a time-dependent manner in CCI rats. MiR-181c-5p was effectively electroporated and highly detected in MSC-derived Exos. ExomiR-181c-5p internalized by microglia cells and inhibit the secretion of inflammation factors. ExomiR-181c-5p intrathecal administration alleviated neuropathic pain and neuroinflammation response in CCI rats. Taken together, ExomiR-181c-5p alleviated CCI-induced NP by inhibiting neuropathic inflammation. ExomiR-181c-5p may be a valid alternative for the treatment of neuropathic pain and has vast potential for future development.